Drying and Preserving Plant Materials for Decorative Uses - Sydney Park Brown; Patricia White; Benny Tjia; Marion R. Sheehan (EDIS)
Dried and preserved plant materials are popular for home decor. Dried arrangements can preserve the graceful lines, textures, and colors of flowers and foliage with a subtle and gently aged appearance. This 14-page fact sheet was written by Sydney Park Brown, Patricia White, Benny Tjia, Marion R. Sheehan, and published by the UF Department of Environmental Horticulture, November 2013. http://edis.ifas.ufl.edu/ep004